Analysis of high dimensional data from intensive care medicine - Marcus Bauer; Ursula Gather; Michael Imhoff (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
As high dimensional data occur as a rule rather than an exception in critical care today, it is of utmost importance to improve acquisition, storage, modelling and analysis of medical data, which appears feasible only with the help of bedside computers. The use of clinical information systems offers new perspectives of data recording and also causes a new challenge for statistical methodology. A graphical approach for analysing patterns in statistical time series from online monitoring systems in intensive care is proposed here as an example of a simple univariate method, which contains the possibility of a multivariate extension and which can be combined with procedures for dimension reduction.
Keywords: 519; Clinical information systems; decision support; high dimensional time; series; online monitoring; phase space reconstruction